2009
DOI: 10.1117/1.3269676
|View full text |Cite
|
Sign up to set email alerts
|

In vivo harmonic generation biopsy of human skin

Abstract: The ability to in vivo image deep tissues noninvasively with a high resolution is strongly required for optical virtual biopsy. Higher harmonic generation microscopy, combined with second- and third-harmonic generation microscopies, is applied to 17 Asian volunteers' forearm skin. After continuous observation for 30 min, no visible damage was found. Our study proves that harmonic generation biopsy (HGB) is able to satisfy the safety requirement and to provide high penetrability (approximately 300 microm) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 21 publications
4
90
0
Order By: Relevance
“…[27][28][29][30][31][32][33][34] Based on the principle of third-order nonlinear processes, the melanin-enhancement nature of label-free third-harmonic generation (THG) in HGM has been confirmed in the previous study. 28 We have also demonstrated that HGM achieved high diagnostic accuracy in nonmelanoma pigmented skin lesions such as BCC, SK, and melanocytic nevus.…”
Section: -3mentioning
confidence: 97%
See 2 more Smart Citations
“…[27][28][29][30][31][32][33][34] Based on the principle of third-order nonlinear processes, the melanin-enhancement nature of label-free third-harmonic generation (THG) in HGM has been confirmed in the previous study. 28 We have also demonstrated that HGM achieved high diagnostic accuracy in nonmelanoma pigmented skin lesions such as BCC, SK, and melanocytic nevus.…”
Section: -3mentioning
confidence: 97%
“…In the histopathological examinations, no evidence of photodamage, such as coagulation necrosis, on the illuminated specimens was identified. 27,28,31-34…”
Section: Third-harmonic Generation Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…THG has the potential to complement these existing imaging approaches. The applicability of THG in optical biopsies has been demonstrated in hamster and human oral mucosa, as well as human skin and adipose tissue (Chen et al, 2009;Tai et al, 2005Tai et al, , 2006Tsai et al, 2011Tsai et al, , 2013. Furthermore, the image contrast generated using THG is suitable for discriminating melanoma and basal cell carcinoma lesions from normal skin and benign nevi .…”
Section: Virtual Optical Biopsymentioning
confidence: 99%
“…The high image contrast results from a difference between strong light absorption of nucleic acids and weak absorption of protein, which reaches the maximum at a wavelength of 250 nm. In addition to UV-PAM, several other modern optical microscopy technologies have been explored for in vivo imaging of unstained cell nuclei, such as reflectance confocal microscopy [8][9][10][11], multiphoton microscopy [12][13][14], and third-harmonic generation microscopy [15,16], However, reflectance confocal microscopy is difficult to provide specific image contrast for nuclei [8], multiphoton microscopy produces in vivo images of cell nuclei with negative contrast [13], and third harmonic generation microscopy generates nuclear images with low contrast [15].…”
Section: Discussionmentioning
confidence: 99%